Age is no barrier: predictors of academic success in older learners. (December 2017) - Imlach, Abbie-Rose; Ward, David; Stuart, Kimberley; Summers, Mathew; Valenzuela, Michael; King, Anna; Saunders, Nichole; Summers, Jeffrey; Srikanth, Velandai; Robinson, Andrew; Vickers, James
Abstract Although predictors of academic success have been identified in young adults, such predictors are unlikely to translate directly to an older student population, where such information is scarce. The current study aimed to examine cognitive, psychosocial, lifetime, and genetic predictors of university-level academic performance in older adults (50–79 years old). Participants were mostly female (71%) and had a greater than high school education level (M = 14.06 years, SD = 2.76), on average. Two multiple linear regression analyses were conducted. The first examined all potential predictors of grade point average (GPA) in the subset of participants who had volunteered samples for genetic analysis (N = 181). Significant predictors of GPA were then re-examined in a second multiple linear regression using the full sample (N = 329). Our data show that the cognitive domains of episodic memory and language processing, in conjunction with midlife engagement in cognitively stimulating activities, have a role in predicting academic performance as measured by GPA in the first year of study. In contrast, it was determined that age, IQ, gender, working memory, psychosocial factors, and common brain gene polymorphisms linked to brain function, plasticity and degeneration (APOE, BDNF, COMT, KIBRA, SERT ) did not influence academic performance. These findings demonstrate that ageing does not impede academic achievement, and that discrete cognitive skills as well as lifetime engagement in cognitively stimulating activities can promote academic success in older adults. University: who performs better in later life? Mental activity and select cognitive domains are better predictors of academic performance in later life than previous education or intelligence. Dr. David Ward and a team of researchers from the University of Tasmania and other Australian institutions examined which aspects of older adults predicted performance in a range of university courses. Those who performed better had engaged in more mental activities throughout midlife, such as playing musical instruments or learning a new language, and possessed better memory and language abilities. Previous education only had a limited impact on academic performance, and other factors such as age, intelligence, and gene variations linked to cognition were unrelated to performance. These findings indicate that many of the assumed barriers to education in later life are weaker than anticipated, and highlight opportunities for further education across the lifespan.